Health Care Access of Mentally-Ill Persons: An Integrative Literature Review - Panes, Iril I. (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
This integrative literature review explores the health care access of mentally-ill persons. Using different databases and search engines, an exhaustive web-based search was conducted. From the initial search, one hundred fiftyseven (157) articles published between the years 2010-2017, in English, and focused on the health care access of mentally-ill were extracted. After removal of duplicates, 42 articles were obtained, of which 23 were included in the final synthesis. Results reveal that personal factors of health-seeking behaviors, awareness, financial problems and cultural influence, as well as environmental factors that includes human and institutional resource, fragmented health care system and governmental policies serve as barriers to mental health care access. Improving community awareness, strengthening the interconnected relationships of mental health policy and health workforce management are components that could provide a useful approach to address the problem in accessibility. Future researches and other scholarly pursuit should give emphasis on the concepts of family, mental illness, and quality of life; as well health system strengthening and policy-making. Furthermore, issues on political, economic and cultural barriers have so long impeded global mental health care and resulted in treatment gaps should be future priorities within the context of research, education, and policy. Keywords: Mental illness, Mental health, Access to care, Mental health care access